Comparing the efficacy of different types of exercise therapy in patients with essential hypertension: a systematic review and network meta-analysis - Liu, Longcheng; Wang, Jiale; Ji, Xiaodi; Wang, Anqi; Yang, Shuo; Chi, Xiaojian; Hu, Lingqian; Zhang, Baolin; Ma, Lihong (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo compare the efficacy of different types of exercise modalities such as Tai Chi, Baduanjin, and Aerobic exercise in the treatment of hypertension.MethodsThis article retrieved randomized controlled trials (RCTs) from the establishment of databases such as CNKI, WanFang, VIP, CBM, PubMed, Embase, Web of Science, and Cochrane Library to December 9, 2024. After assessing the risk of bias using the Cochrane risk of bias tool, a network meta-analysis was performed using Rev Man 5.4 and Stata 15 software. The primary outcome indicator of this article is Ambulatory Blood Pressure Measurement (ABPM), which includes 24-h average systolic blood pressure (SBP) and 24-h average diastolic blood pressure (DBP).ResultsA total of 63 RCTs meeting the criteria were included, involving 5,663 patients. The network meta-analysis results showed that compared with the control group, Light-intensity continuous training (LIAE)+antihypertensive medication [WMD = −1.82, 95%CI(−2.93, −0.71)] was the most effective intervention for lowering SBP. For lowering DBP, Wuqinxi + antihypertensive medication [WMD = −2.78, 95% CI (−4.1,−1.45)] was the most effective intervention. And the differences were statistically significant (P < 0.05).ConclusionExercise therapy combined with antihypertensive drugs may achieve a more significant blood pressure-lowering effect, and LICT, Wuqinxi, and Liuzijue may be higher priority options.Systematic Review Registrationhttp://wwwcrdyork.ac.uk/PROSPERO/, PROSPERO CRD42024626332.